Existence of the solution family of a system of linear difference equations with an argument deviation - Mardanov , I. Dzh. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Sufficient conditions for the existence of a family of solutions of a system of linear difference equations with deviating argument are obtained.